Constitutional Safeguards And National Resilience: A Qualitative Analysis of Article 153 In Malaysia’s Multi-Ethnic Society - Mohd Hisyamuddin Basabah; Kamarul Zaman Haji Yusoff; Mohamad Isa Abd Jalil; Suddin Lada; Shariff Umar Shariff Abd. Kadir; Debrina Puspita Andriani (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Article 153 of the Federal Constitution of Malaysia is a vital constitutional instrument in governing a multi-ethnic nation; however, ongoing political and identity dynamics have raised questions regarding its contribution to national resilience. This study aims to analyze the function of Article 153 as a constitutional safeguard in maintaining societal security and Malaysia's national resilience during the 2018–2024 period, while identifying the mechanisms, tensions, and factors influencing its effectiveness. Employing a qualitative approach, the research conducted semi-structured interviews with five experts in constitutional law, ethnic relations, and national security, supplemented by an analysis of policy documents, court rulings, and academic literature, validated through triangulation. The findings reveal that Article 153 contributes to national resilience through four primary mechanisms: the protection of collective Bumiputera identity, affirmative economic redistribution, balanced regional development, and political stabilization via elite consensus. Nevertheless, structural tensions persist between protective measures for Bumiputera and demands for inclusivity from non-Bumiputera communities, which intensified during the 2018–2024 political crises due to the re-securitization of ethnic identity. Comparative analysis with Rwanda, Sri Lanka, India, and South Africa highlights the strengths of the Malaysian model in terms of constitutional entrenchment and the dual protection mechanism involving the constitutional monarchy. The effectiveness of Article 153 fundamentally depends on three determinant factors: government political will, public constitutional literacy, and economic performance that sustains redistribution. This research recommends implementation reforms focused on enhancing constitutional awareness, increasing transparency in need-based affirmative policies, and institutionalizing inter-ethnic dialogue to achieve inclusive and sustainable national resilience.